The Effectiveness of “Kartun Anak” Youtube Channel As A Learning Media to Teach Vocabulary - Hestiana Nur Az-zahra; Rika Septiani, Rika Septiani; Jajat Imanudin, Jajat Imanudin (Jurnal Fakultas Keguruan & Ilmu Pendidikan Kuningan, 2024)
Vocabulary is the most important component for improving language skills. Teachers need tools or media to support learning during the learning process. Learning media is anything that can be used as a tool for teaching. For the vocabulary learning process in this study used the “Kartun Anak” YouTube channel. The aims of this study is to determine the effectiveness and students engagement in the use of the “Kartun Anak” YouTube channel as a learning medium to teach vocabulary in the fourth grade students of SDN 1 Cikaduwetan. This study used quantitative pre-experimental methods with a pre-test and post-test one-group design. The population and sample in this study were students in the fourth grade, for a total of 35 students. This sampling technique used saturated sampling. Data collection used instruments pre-test, post-test, observation, and documentation. The results showed that the use of the “Kartun Anak” YouTube channel as a medium for learning vocabulary in the fourth grade is effective in improving students’ vocabulary mastery. This can be proven by the mean post-test score (82.42), which is higher than the mean pre-test score (51.57). “Kartun Anak” YouTube channel has a good effect on students. The reason this YouTube channel can help improve students’ vocabulary is because the results of observations show that student engagement is positive and very interesting to make students enjoy in learning vocabulary.